SOCIAL MEDIA AND VIRAL MARKETING ANALYSIS OF PURCHASE DECISIONS THROUGH TIKTOK APPLICATIONS - Aulia Asri Fawwazi Haryanto; Kokom Komariah; R Deni Muhammad Danial (Inovbiz: Jurnal Inovasi Bisnis, 2021)
The purpose of this study was to determine the effect of social media and viral marketing on purchase decisions through tiktok apps. The method used in this research is descriptive method and associative method with a quantitative approach. The sampling technique in this study used non-probability sampling with purposive sampling type, and in this case only 190 respondents. The data analysis technique used is multiple linear regression analysis, including the coefficient of determination test, multiple correlation coefficient, simultaneous test (F test) and partial test (T test). The results of the study, using the F test the probability value of sig. 0.00 < 0.05 which means that together social media and viral marketing have a significant influence on purchase decisions. While the t test shows that social media has a significant influence on purchase decisions and viral marketing has a significant influence on purchase decisions.